The beta recombinase from the Streptococcal plasmid pSM 19035 represses its own transcription by holding the RNA polymerase at the promoter region. - Rojo, F (1994)
The beta protein encoded by the Streptococcus pyogenes plasmid pSM19035 is a site-specific recombinase involved in both resolution of plasmid multimers into monomers and DNA inversion. It has been proposed that the DNA region to which the beta recombinase binds to mediate recombination includes a promoter from which orf alpha and the beta gene are transcribed. We have determined the sites at which transcription of the orf alpha and the beta gene initiates in vitro and we have demonstrated that highly purified beta recombinase acts as a repressor of its own synthesis. The promoters are located within the beta recombinase binding site, which we have defined previously. The binding of the beta recombinase to its target site does not seem to exclude RNA polymerase from the promoter, despite the overlapping of their binding sites. Therefore, it is likely that the beta recombinase does not repress transcription by a mere steric hindrance on RNA polymerase binding.